2021
DOI: 10.1136/bmjopen-2020-045458
|View full text |Cite
|
Sign up to set email alerts
|

Geographical variations and factors associated with recent HIV testing prevalence in Ghana: spatial mapping and complex survey analyses of the 2014 demographic and health surveys

Abstract: ObjectiveTo examine the factors associated with recent HIV testing and to develop an HIV testing prevalence surface map using spatial interpolation techniques to identify geographical areas with low and high HIV testing rates in Ghana.DesignSecondary analysis of Demographic and Health Survey.SettingRural and urban GhanaParticipantsThe study sample comprised 9380 women and 3854 men of 15–49 years.ResultsWe found that 13% of women and 6% of men of Ghana had tested for HIV in the past 12 months. For women, being … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 37 publications
4
10
1
Order By: Relevance
“…Specifically, reproductive women who reported a positive history of STI infection have higher odds of testing for HIV compared to those who do not. This finding agrees with findings from a study conducted in Ghana [42] where women who reported previous history of STIs were more likely to test for HIV. Furthermore, this study revealed largely homogeneity in HIV testing across rural-urban population in the Gambia.…”
Section: Discussionsupporting
confidence: 92%
“…Specifically, reproductive women who reported a positive history of STI infection have higher odds of testing for HIV compared to those who do not. This finding agrees with findings from a study conducted in Ghana [42] where women who reported previous history of STIs were more likely to test for HIV. Furthermore, this study revealed largely homogeneity in HIV testing across rural-urban population in the Gambia.…”
Section: Discussionsupporting
confidence: 92%
“…In that study, the following subgroups had higher HIV testing rates compared with the national average of 13%: Women aged 25-34 years (19%); those married (16%); those with previous STIs (16%), those with only one sexual partner (16%); from richest households (18%); and those with higher than secondary education (26%). Clearly, age, education, marital status, income and sexual behaviour influenced HIV testing among men and women aged 15 to 49 years in the general population of Ghana [19]. The estimates obtained compared well with the previous estimates by Tenkorang & Owusu (2010) [18].…”
Section: Plos Global Public Healthsupporting
confidence: 77%
“…Tenkorang & Owusu (2010) found a 10% prevalence of HIV testing among women in the general population of Ghana [18]. Secondary analysis of data from the nationally representative, 2014 Ghana Demographic and Health Survey found a low HIV testing prevalence rate of 13% among women and 6% among men aged 15 to 49 years in the 12 months period preceding the survey [19]. Wide variations in HIV testing rates were observed among sub-groups of the population, within regions and across the 10 regions of the country.…”
Section: Plos Global Public Healthmentioning
confidence: 99%
“…Negative association in perception of excellent health with HIV/AIDS self-testing uptake is more prevalent around various districts across the country including West Coast, Namakwa, Vhembe, Capricorn, Waterberg, Mangaung, Gert Sibande, and Thabo Mofutsanyane. The lack of a strong relationship between the perception of excellent health and HIV/AIDS self-testing uptake could be attributed to fear of denunciation and a loss of emotional control because of the mental burden of knowing one’s HIV/AIDS positive status [ 11 , 20 ]. Equally important, the fear of having a positive result without any immediate personal support can be devastating to people, thus the increased hesitancy in self-testing uptake [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have explored the association of HIV testing uptake with spatial patterns, socioeconomic status, and demographics, etc., [ 2 , 3 , 4 , 7 , 11 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. For instance, Ntsepe et al [ 4 ] analysed people’s perceptions of HIV testing in formal and informal urban communities from different races and age groups in select towns (Cape Town and Durban) across two South African provinces.…”
Section: Introductionmentioning
confidence: 99%